Optimizing ETL Pipelines with Informatica: Performance, Scalability, and Governance (Journal of Science & Technology, 2020)
The purpose of this paper is to explore the optimization of ETL (Extract, Transform, Load) pipeline using Informatica tools which focuses on performance, scalability, and governance. This paper’s objective is to explore the best strategies in the design, development, and administration of data integration by leveraging industry standard tools like Informatica PowerCenter, Informatica Test Data Management, Informatica Data Quality, Informatica Master Data Management, and Informatica Data Management Cloud (IDMC). Using these tools optimization of data transformation efficiency through efficient data processing techniques, workflow automation, and robust scripting, mainly using Unix shell scripting.